2010
DOI: 10.1007/s00264-010-1019-3
|View full text |Cite
|
Sign up to set email alerts
|

Management of the infected shoulder prosthesis: a retrospective analysis and review of the literature

Abstract: Experience with infected shoulder arthroplasty is limited. Treatment options are either one-or two-stage reimplantation, débridement with retention of the prosthesis, resection arthroplasty or arthrodesis. We retrospectively analysed ten patients with an infected shoulder prosthesis and evaluated the diagnostic and therapeutic management as well as the clinical outcome, assessed by the Constant score, Neer's criteria and the mean abduction ability. We identified an infecting organism before surgery in nine pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
2
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 30 publications
2
49
2
7
Order By: Relevance
“…This finding is not surprising and has been previously described in periprosthetic infections after hip and knee replacement [20,21]. On the other hand, intraoperative microbiology examination, even if performed without ultrasound, nearly doubled the chances of isolating the causative micro-organism; this finding is different from that reported by Weber et al [19], which showed a 100% positive intraoperative cultural examination, but is consistent with many other studies, where only a variable percentage of all intraoperative swabs showed positive growth [3,4,6,9,10]. Our organism spectrum was similar to that reported in most other studies, with Staphylococcus and Propionibacterium spp.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…This finding is not surprising and has been previously described in periprosthetic infections after hip and knee replacement [20,21]. On the other hand, intraoperative microbiology examination, even if performed without ultrasound, nearly doubled the chances of isolating the causative micro-organism; this finding is different from that reported by Weber et al [19], which showed a 100% positive intraoperative cultural examination, but is consistent with many other studies, where only a variable percentage of all intraoperative swabs showed positive growth [3,4,6,9,10]. Our organism spectrum was similar to that reported in most other studies, with Staphylococcus and Propionibacterium spp.…”
Section: Discussioncontrasting
confidence: 56%
“…Although different treatment options have been reported, a consensus about the best therapeutic strategy is still lacking [19]. To our knowledge, this is the largest continuous series of infected shoulder prosthesis ever reported.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Seul Beekman et al (30) a rapporté une série de 10 infections sur prothèse inversée, traitées par révision en 1 temps, avec 100% de guérison et un résultat fonctionnel satisfaisant. Plusieurs auteurs ont en revanche étudié les résultats de ces révisions dans les infections de prothèses d'épaule non contraintes, avec des taux de guérison allant de 63 à 100% (21,(31)(32)(33)(34)(35)(36)(37)(38) . Le résultat fonctionnel rapporté est le plus souvent meilleur qu'en pré-opératoire, mais variable selon les séries : Coste et al (21) obtient un CS moyen à 66 après révision en 1 temps, et 35 après révision en 2 temps, Jerosh et al (38) un CS à 48 sur une série comprenant une majorité de traitement en 2 temps, et récemment Klatte et al (31) un CS de 43 à 61 après traitement en 1 temps, selon le type de prothèse réimplantée (respectivement hémi ou inversée).…”
Section: Discussionunclassified
“…Other microorganisms such as enterococci, streptococci, corynebacterium, fungal species and mycobacterial species are reported less commonly [3,27]. Of note, the microbiology of prosthetic joint infection differs between upper limb and lower limb arthroplasty: Propionibacterium acnes is one of the most common microorganisms encountered in shoulder prosthetic joint infection, occurring in up to 40% of shoulder arthroplasty infections [16,28,29]. This association may be due to the increased occurrence of Propionibacterium acnes around the head and neck, in particular in the sebaceous glands and hair bulbs [12].…”
Section: Microbiologymentioning
confidence: 99%